Aceh Growth Diagnostic : Identifying the Binding Constraints to Growth in a Post-Conflict and Post-Disaster Environment - World Bank (Washington, DC, 2014)
This report shows that some investors still perceive Aceh as a risky place to do business, despite being relatively peaceful for almost four years. Security incidents, relatively common in post-conflict environments, deter businesses and individuals from investing in Aceh, robbing the economy of necessary capital and innovation. Other consequences of the conflict, including forms of illegal taxation, also hurt investment. The Government of Aceh is aware that until businesses and people change their perceptions of security in Aceh and feel confident that they can reap the full benefits of their investments, little investment will be forthcoming. As a result, growth in the province will be limited and efforts to reduce poverty less effective. There are other problems affecting Aceh's economy. These include the business environment, access to capital and the quality of infrastructure. This report seeks to show how these different factors affect investment and growth, and provides recommendations on how the Government might prioritize and sequence policy changes to improve the investment climate.